Unusual Suspect: A Case Report of Tubulocystic Renal Cell Carcinoma with Features of Cystic Renal Oncocytoma - Jacob D. McFadden; Isabell A. Sesterhenn; Sean Q. Kern (Case Reports in Urology)
Tubulocystic renal cell carcinoma is an uncommon subtype of renal cell carcinoma that was only recently acknowledged by the World Health Organization. There is a relatively small collection of literature dedicated to the features and clinical course of this lesion. Despite its rarity, this diagnosis should remain in the differential for all cystic renal masses. We present a case report of tubulocystic renal cell carcinoma (TC-RCC) with remarkable similarity to cystic renal oncocytoma, highlighting the diagnostic challenges associated with this unusual renal malignancy.